2021
DOI: 10.1038/s41598-021-84814-5
|View full text |Cite
|
Sign up to set email alerts
|

High turbidity levels alter coral reef fish movement in a foraging task

Abstract: Sensory systems allow animals to detect and respond to stimuli in their environment and underlie all behaviour. However, human induced pollution is increasingly interfering with the functioning of these systems. Increased suspended sediment, or turbidity, in aquatic habitats reduces the reactive distance to visual signals and may therefore alter movement behaviour. Using a foraging task in which fish (Rhinecanthus aculeatus) had to find six food sites in an aquarium, we tested the impact of high turbidity (40–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Also, due to the fact that tasks become fully automated, it reduces the chance of human errors. Moreover, in combination with the automation, its low cost (Figure 1a, Table 1) We stress that the experimental configuration presented here (a Y-maze setup for two alternative forced choice reversal learning and colour discrimination tasks) is a proof-of-concept but that GoFish's basics could be used without configural changes in multiple other experimental paradigms e.g., quantity discrimination experiments (Potrich et al, 2022;Schluessel et al, 2022), behavioural timing (Talton et al, 1999, foraging (Aw et al, 2009;Newport et al, 2021), object recognition (Newport et al, 2016), and navigation (Burt de Perera & Holbrook, 2012;Newport et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, due to the fact that tasks become fully automated, it reduces the chance of human errors. Moreover, in combination with the automation, its low cost (Figure 1a, Table 1) We stress that the experimental configuration presented here (a Y-maze setup for two alternative forced choice reversal learning and colour discrimination tasks) is a proof-of-concept but that GoFish's basics could be used without configural changes in multiple other experimental paradigms e.g., quantity discrimination experiments (Potrich et al, 2022;Schluessel et al, 2022), behavioural timing (Talton et al, 1999, foraging (Aw et al, 2009;Newport et al, 2021), object recognition (Newport et al, 2016), and navigation (Burt de Perera & Holbrook, 2012;Newport et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We stress that the experimental configuration presented here (a Y-maze setup for two alternative forced choice reversal learning and colour discrimination tasks) is a proof-of-concept but that GoFish ’s basics could be used without configural changes in multiple other experimental paradigms e.g., quantity discrimination experiments (Potrich et al, 2022; Schluessel et al, 2022), behavioural timing (Talton et al, 1999), foraging (Aw et al, 2009; Newport et al, 2021), object recognition (Newport et al, 2016), and navigation (Burt de Perera & Holbrook, 2012; Newport et al, 2016). GoFish could also be used to implement experiments using a range of set-ups differing to that reported here (e.g., open field and maze configurations that could employ a greater number of screens and/or feeders than we have).…”
Section: Discussionmentioning
confidence: 99%
“…Given that movement underpins essential behaviors including as feeding, mating and predator avoidance, a decrease in movement efficiency is anticipated to have a considerable influence on the health and population dynamics of visually guided fish species (Susannah et al 2011 ). The effects of increased sediment suspension on photosynthetic species have been studied; however, there is growing evidence that fish are also significantly impacted (Newport et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial community dwelling in the aquatic ecosystem degrades the organic matter present at the bottom through DO consumption (Moresco et al 2012 ; Fuhrman et al 2015 ). First, turbidity affects dissolved oxygen (DO) sources by limiting light penetration and hence photosynthetic activity, as well as gas exchange with the atmosphere (Schmidt et al 2019 ; Newport et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasingly turbid ocean may have negative consequences for oceanic consumers that use visual cues for prey capture. Some fishes have reduced movement efficiency when foraging in turbid conditions [ 8 , 9 ], and one study found that fish biomass in the North Sea was 76–85% positively correlated with water visibility alone [ 10 ], suggesting that visibility is pivotal in the habitat preference of many fish species. In addition, species compositions can be altered by elevated turbidity in coastal systems, where visual predators are put at a disadvantage compared to chemosensory predators [ 11 ].…”
Section: Introductionmentioning
confidence: 99%